KESINAMBUNGAN DAN PROSES TRANSMISI KELENTANGAN DALAM KONTEKS RITUAL MASYARAKAT DAYAK BENUAQ DI KALIMANTAN TIMUR - Eli Irawati; Wisma Nugraha; Timbul Haryono (Institut Seni Indonesia Yogyakarta, 2017)
Transmission is one of the notable issues due to its role in the continuity of local-traditional musical practices across the globe. This paper aims to explore the transmission of kelentangan music and its link with the continuity of the music.Using ethnographic approach, this study deal with kelentangan not merely as musical sound but as a results of music making and varius activities in the daily life of Benuaq people. This study shows that, firstly, transmission of knowledge and skilss od kelentangan occurred between penu’ung to penu’ung and between penu’ung and its audiences. The second, kelentangan is closely tied with the extra-musical contexts. There has been no specific learning institution in Dayak Benuaq culture to the teaching and learning of the music. The third, the transmission of kelentangan not only generates the regenerations of its musicians, but also of its audiences. Last but not least, transmission has been one of notable elemets of the continuity of music. Transmission however cannot be operating in itself. It instead closely tied to various extra-musical context and activities in the life of Benuaq people, ranging from profane to the sacred one. In other words, it is located in the ecosystem of culture of Benuaq people. The transmission of kelentangan takes place in part due Benuaq peopleare still remain conduct their culture in line with their ancestors life in the past. Thus, to maintain the continuity of kelentangan music means to maintain the ecosystem of culture of Benuaq people. Keywords: Kelentangan, Transmission, Continuity, Contexts, Ecosystem of Culture